Protamine Neutralization of the Release of Tissue Factor Pathway Inhibitor Activity by Heparins - Harenberg, Job; Siegele, Marietta; Dempfle, Carl-Erik; Stehle, Gerd; Heene, Dieter L (Thrombosis and Haemostasis, 1993)
The present study was designed to investigate the action of protamine on the release of tissue factor pathway inhibitor (TFPI) activity by unfractionated (UF) and low molecular weight (LMW) heparin in healthy individuals. 5000 IU UF-heparin or 5000 IU LMW-heparin were given intravenously followed by saline, 5000 U protamine chloride or 5000 U protamine sulfate intravenously after the 10 min blood sample. Then serial blood samples for the measurement of TFPI activity and anti-factor Xa- activity were taken, in order to detect a possible relation between the remaining anti-factor X a activity after neutralization of LMW-heparin with protamine and TFPI activity and to establish whether or not a rebound phenomenon of plasmatic TFPI occurs.There was no difference in the release and in the kinetics of TFPI by UF- and LMW-heparin with subsequent administration of saline. After administration of protamine TFPI activity decreased immediately and irreversibly to pretreatment values. There were no differences between protamine chloride and protamine sulfate on the effect of TFPI induced by UF- or LMW-heparin. No rebound phenomenon of TFPI activity occurred. In contrast anti-factor Xa- activity, as measured by the chromogenic S2222-assay, issued the known differences between UF- and LMW-heparin. The half-life of the aXa-effect of LMW-heparin was twice as long as of UF-heparin. Protamine antagonized UF-heparin completely and about 60% of the anti-factor Xa activity of LMW-heparin, using chromogenic S2222-method. No differences could be detected for protamine chloride and sulfate form of protamineIt is assumed that protamine displaces heparins from the binding sites of TFPI. There were no differences between UF- and LMW-heparin. The data indicate that the sustained antifactor Xa activity after antagonization of LMW-heparins as well as heparin rebound phenomena are not mediated by TFPI activity.